Influência do processamento dos grãos sobre a qualidade da silagem de milho - Zmijevski, André Favero (2024)
The objective was to evaluate the influence of grain processing on the quality of corn silage. The present work was carried out in the state of Paraná, based on the analysis of 90 samples of corn silage from different rural properties that practice beef and dairy cattle farming. The experimental design used was quite randomized, with three treatments. The treatments are different degrees of grain processing: Excellent: > 70%; Adequate: 50 – 69%; Inadequate: < 50%. The samples were removed from the face of the silo, vacuum packed and sent to the Esalq-Pirassununga Animal Nutrition Laboratory for KPS, NIR and Penn State analysis. The acetic acid content (P<0.05) presented higher values for the appropriate category. Starch analysis showed that silages with Inadequate and Adequate KPS have a higher starch concentration (P<0.05). Neutral detergent fiber and acid detergent fiber were higher in the excellent category (P<0.05). The dry matter theory presents lower values in the appropriate category (P<0,05). Milk production per ton of silage dry matter showed higher productions in the adequate and inadequate categories (P<0.05). The grain processing content has an influence on the quality of the silage, showing higher milk production per ton of dry matter in the category with “adequate” grain processing.